“EMERGING VIRAL DISEASES: AN OVERVIEW” (International Journal of Food and Nutritional Sciences, 2021)
Emerging viral diseases have become a significant concern for global public health, posingthreats to human health, economies, and ecosystems. Emerging viral diseases (EVDs) haveincreasingly become a pressing concern for global public health, posing substantial threats notonly to human health but also to economies and ecosystems. These diseases, often originatingfrom zoonotic sources, rapidly spread through populations, leading to significant morbidity andmortality. The COVID-19 pandemic is a stark example, highlighting how quickly a novel virusdisrupt health systems and economies worldwide. This paper explores the nature of emergingviral diseases, factors contributing to their emergence, and the challenges associated with theirmanagement and prevention. Through a review of current literature and case studies, the paperhighlights the importance of surveillance, research, and international cooperation in addressingthese threats. Key findings indicate that rapid urbanization, environmental changes, andincreased human-animal interactions are critical factors in the emergence of new viral pathogens.